Multidrug-Resistant (MDR) bacterial pathogens in ventilator associated pneumonia at tertiary care hospital - Harsha V. Patil, Shivaji T Mohite, Virendra C. Patil (International Journal of Advanced Science and Technology, 2020)
Background: Multi-drug resistant (MDR) Ventilator associated pneumonia (VAP) is becoming more frequent in Intensive Care Unit. There is inadequate clinical data from Indian ICUs on the incidence of MDR VAP. Aims: To determine the bacteriology, antibiotic susceptibility pattern and multi-drug resistant (MDR) organism causing VAP. Materials and Methods: This was a prospective- observational study conducted in medical ICUs of tertiary care -teaching institute over a period of 2 year (January 2015– December 2016). The patients satisfying the criteria of VAP were included in this study. A clinical suspicion of VAP was made in patients with a modified clinical pulmonary infection score (CPIS) >6. Statistical analysis was performed using SPSS trial version 21.0 software and the values of P < 0.05 were considered statistically significant. Results: Total 624 (49.88%) patients developed VAP. The overall VAP rate per 1000 ventilator days was 29.72. Gram negative bacteria (Klebsiella spp, P. aeruginosa, Acinetobacter, E. coli) were frequently compared to Gram positive (Coagulase positive Staphylococcus) [‘p’<0.001]. A total 42.95% of VAP was caused by MDR organism. MDR due to Acinetobacter spp (76.42%) was outnumbered compared to other GNB (‘p’<0.002). MDR organisms were more frequent in late onset VAP. Total 27.88% were early onset and 72.12% were late onset VAP (‘p’ < 0.001). Prolonged duration of ventilation, prior use of antimicrobial agents, co-morbidites, unconscious state were the risk factors for developing MDR VAP. Overall case fatality rate was 6.89%. Total 31 (11.56%) patients succumbed among MDR -VAP (‘p’<0.032). Colstin, Tigecycline and Meropenem had better sensitivity for Gram negative bacteria while Linezolid and Vancomycin were better for Gram positive isolates (COPS/ MRSA). Conclusions: Acinetobacter spp, Klebsiella spp, P. aeruginosa and E. coli were the most frequent organisms with high mortality rates in present study. Prior antibiotic therapy, prolong duration of ventilation and comorbidities were associated with MDR organisms. There was a high incidence of MDR pathogens in late-onset VAP.